Long Range Correlated Motions of TIM and their Possible Influence on Enzyme Function - McKinney, J. A.; Deng, Y. T.; George, D. K.; Richard, J.; Markelz, A. G. (Biophysical Journal, 2020)
The alpha-beta barrel structure of triosephosphate isomerase (TIM) is possibly the most common among enzymes. In the case of TIM, structural dynamics are known to be essential to function. In particular the stabilization of the binding pocket by a phosphodianion “handle” of the substrate and the closing of catalytic site loops 6 and 7 over the substrate. Loop 6 moves by as much as 7 Angstroms with binding. Recently a mutant survey for human TIM (hsTIM) found kcat can change significantly for a single mutation distant from the catalytic site. Crystallographic measurements find no structural change with the mutation, suggesting a dynamical mechanism for the allosteric effect. Here we use Stationary Sample Anisotropic Terahertz Microscopy (SSATM) to measure the long-range intramolecular vibrations and determine if specific vibrations couple the allosteric and catalytic sites. SSATM isolated protein long-range structural vibrations based on the dominant displacement direction [1-4]. We examine if specific vibrational bands are associate with loop 6 and loop 7 flexibility.
ISI Document Delivery No.: KK8YX Times Cited: 0 Cited Reference Count: 4 Cited References: Acbas G, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms4076 Niessen K.A. M.Y., 2017, BIOPHYS J, DOI [10.1016/j.bpj.2016.12.049.3., DOI 10.1016/J.BPJ.2016.12.049.3] Niessen K, 2019, OPT EXPRESS, V27, P28036, DOI 10.1364/OE.27.028036 Niessen KA, 2019, NAT COMMUN, V10, DOI 10.1038/s41467-019-08926-3 McKinney, Jeffrey A. Deng, Yanting George, Deepu K. Richard, John Markelz, Andrea G. 64th Annual Meeting of the Biophysical-Society Feb 15-19, 2020 San Diego, CA Biophys Soc NSFNational Science Foundation (NSF) [DBI 1556359, MCB 1616529]; DOEUnited States Department of Energy (DOE) [DE-SC0016317]; NIH STTRUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USA [R41 GM125486.1] This work is supported by NSF grants DBI 1556359 and MCB 1616529, DOE grant DE-SC0016317 and NIH STTR R41 GM125486.1. 1 Cell press Cambridge 1542-0086
Keywords: Biophysics

Persistent Protein Motions in a Rugged Energy Landscape Revealed by Normal Mode Ensemble Analysis - Romo, T. D.; Grossfield, A.; Markelz, A. G. (Journal of Chemical Information and Modeling, 2020)
Proteins are allosteric machines that couple motions at distinct, often distant, sites to control biological function. Low-frequency structural vibrations are a mechanism of this long-distance connection and are often used computationally to predict correlations, but experimentally identifying the vibrations associated with specific motions has proved challenging. Spectroscopy is an ideal tool to explore these excitations, but measurements have been largely unable to identify important frequency bands. The result is at odds with some previous calculations and raises the question what methods could successfully characterize protein structural vibrations. Here we show the lack of spectral structure arises in part from the variations in protein structure as the protein samples the energy landscape. However, by averaging over the energy landscape as sampled using an aggregate 18.5 mu s of all-atom molecular dynamics simulation of hen egg white lysozyme and normal-mode analyses, we find vibrations with large overlap with functional displacements are surprisingly concentrated in narrow frequency bands. These bands are not apparent in either the ensemble averaged vibrational density of states or isotropic absorption. However, in the case of the ensemble averaged anisotropic absorption, there is persistent spectral structure and overlap between this structure and the functional displacement frequency bands. We systematically lay out heuristics for calculating the spectra robustly, including the need for statistical sampling of the protein and inclusion of adequate water in the spectral calculation. The results show the congested spectrum of these complex molecules obscures important frequency bands associated with function and reveal a method to overcome this congestion by combining structurally sensitive spectroscopy with robust normal mode ensemble analysis.
ISI Document Delivery No.: PT8QA Times Cited: 0 Cited Reference Count: 47 Cited References: Acbas G, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms4076 Bahar I, 2007, CURR OPIN STRUC BIOL, V17, P633, DOI 10.1016/j.sbi.2007.09.011 Balog E, 2011, J PHYS CHEM B, V115, P6811, DOI 10.1021/jp108493g Castro-Camus E, 2008, CHEM PHYS LETT, V455, P289, DOI 10.1016/j.cplett.2008.02.084 Cerutti DS, 2008, BIOCHEMISTRY-US, V47, P12065, DOI 10.1021/bi800894u Cerutti DS, 2019, WIRES COMPUT MOL SCI, V9, DOI 10.1002/wcms.1402 CHO M, 1994, J CHEM PHYS, V100, P6672, DOI 10.1063/1.467027 Choi JH, 2014, J PHYS CHEM B, V118, P12837, DOI 10.1021/jp508547y Cote Y, 2017, BIOPHYS J, V112, P2575, DOI 10.1016/j.bpj.2017.05.018 Dong J, 1999, ACTA CRYSTALLOGR D, V55, P745, DOI 10.1107/S0907444998016047 ESSMANN U, 1995, J CHEM PHYS, V103, P8577, DOI 10.1063/1.470117 Falconer RJ, 2012, J INFRARED MILLIM TE, V33, P973, DOI 10.1007/s10762-012-9915-9 FELLER SE, 1995, J CHEM PHYS, V103, P4613, DOI 10.1063/1.470648 Gerek ZN, 2011, PLOS COMPUT BIOL, V7, DOI 10.1371/journal.pcbi.1002154 GO N, 1983, P NATL ACAD SCI-BIOL, V80, P3696, DOI 10.1073/pnas.80.12.3696 Grossfield A, 2019, LIVING J COMPUT MOL, V1, P5067, DOI DOI 10.33011/LIVEC0MS.1.1.5067 Grossfield A, 2009, ANN REP COMP CHEM, V5, P23, DOI 10.1016/S1574-1400(09)00502-7 He YF, 2011, BIOPHYS J, V100, P1058, DOI 10.1016/j.bpj.2010.12.3731 HORIUCHI T, 1991, PROTEINS, V10, P106, DOI 10.1002/prot.340100204 Huang J, 2013, J COMPUT CHEM, V34, P2135, DOI 10.1002/jcc.23354 Katebi AR, 2014, PROTEIN SCI, V23, P213, DOI 10.1002/pro.2407 Kindt JT, 1997, J CHEM PHYS, V106, P4389, DOI 10.1063/1.473486 Kroll J, 2007, VIB SPECTROSC, V43, P324, DOI 10.1016/j.vibspec.2006.03.010 Leioatts N, 2012, J CHEM THEORY COMPUT, V8, P2424, DOI 10.1021/ct3000316 Lerbret A, 2009, J CHEM PHYS, V131, DOI 10.1063/1.3273218 Meinhold L, 2007, PHYS REV LETT, V99, DOI 10.1103/PhysRevLett.99.138101 Miller DW, 1999, J MOL BIOL, V286, P267, DOI 10.1006/jmbi.1998.2445 Niessen KA, 2019, NAT COMMUN, V10, DOI 10.1038/s41467-019-08926-3 Niessen KA, 2017, BIOPHYS J, V112, P933, DOI 10.1016/j.bpj.2016.12.049 Phillips JC, 2005, J COMPUT CHEM, V26, P1781, DOI 10.1002/jcc.20289 Porter JR, 2019, BIOPHYS J, V116, P818, DOI 10.1016/j.bpj.2018.11.3144 Romo TD, 2014, J COMPUT CHEM, V35, P2305, DOI 10.1002/jcc.23753 Romo TD, 2009, IEEE ENG MED BIO, P2332, DOI 10.1109/IEMBS.2009.5335065 Sassi P, 2013, J CHEM PHYS, V139, DOI 10.1063/1.4838355 Singh R, 2012, J PHYS CHEM A, V116, P10359, DOI 10.1021/jp307288r Stehle CU, 2012, J CHEM PHYS, V136, DOI 10.1063/1.3686886 STRAUB JE, 1994, J PHYS CHEM-US, V98, P10978, DOI 10.1021/j100093a046 Tehver R, 2009, J MOL BIOL, V387, P390, DOI 10.1016/j.jmb.2008.12.032 Thirumuruganandham SP, 2009, J MOL MODEL, V15, P959, DOI 10.1007/s00894-008-0446-1 Whitmire SE, 2003, BIOPHYS J, V85, P1269, DOI 10.1016/S0006-3495(03)74562-7 Xie AH, 2000, PHYS REV LETT, V84, P5435, DOI 10.1103/PhysRevLett.84.5435 Xu D, 1996, J PHYS CHEM-US, V100, P12108, DOI 10.1021/jp960076a Yu X, 2005, J CHEM PHYS, V122, DOI 10.1063/1.1830431 Yu X, 2004, CHEM PHYS LETT, V391, P181, DOI 10.1016/j.cplett.2004.04.100 Zakaria HA, 2011, APPL SPECTROSC, V65, P260, DOI 10.1366/10-06162 Zhang HL, 2009, J MOL GRAPH MODEL, V27, P655, DOI 10.1016/j.jmgm.2008.10.005 Zorba A, 2019, P NATL ACAD SCI USA, V116, P13937, DOI 10.1073/pnas.1906024116 Romo, Tod D. Grossfield, Alan Markelz, Andrea G. Grossfield, Alan/0000-0002-5877-2789 National Science FoundationNational Science Foundation (NSF) [MCB 1616529]; U.S. Department of EnergyUnited States Department of Energy (DOE) [DESC0016317] Funding was provided by the National Science Foundation (MCB 1616529) and the U.S. Department of Energy (DESC0016317). 1 Amer chemical soc Washington 1549-960x
Keywords: Chemistry; Computer Science; molecular-dynamics; Pharmacology & Pharmacy; photoactive yellow protein; spectroscopy; state; vibrational-modes

Protein Intramolecular Motions with Deuteration and Inhibitor Binding Dependence - Deng, Y.; McKinney, J.; Romo, T.; Grossfield, A.; Markelz, A. G. (APS R63.003, 2019)

Spectral Assignment of Lysozyme Collective Vibrations - Deng, Y. T.; McKinney, J.; Romo, T.; Grossfield, A.; Markelz, A. (Biophysical Journal, 2019)
Global structural vibrations at terahertz (THz) frequencies have been associated with protein function and allosteric control. A chief obstacle to utilizing this control mechanism has been measurement of specific motions. Recently it was shown that while the vibrational density of states, and isotropic absorption spectra are broad and featureless, collective vibrations can be isolated based on their directionality using aligned samples (realized with protein crystals) and anisotropic THz microscopy [1]. However the assignment of resonant bands to specific structural motions was complicated by the high symmetry of the tetragonal crystals used, and the slow experimental method. To structurally map the vibrations of the chicken egg white lysozyme (CEWL) we measure anisotropic absorption of triclinic crystals using our new technique: ideal polarization varying anisotropic THz microscopy (IPV-ATM). The low symmetry triclinic crystals provide absolute protein orientation, and the near field IPV-ATM rapidly measures broadband terahertz linear dichroism of the microcrystals. All measurements were performed at room temperature under 100% humidity conditions. The unit cell parameters of triclinic lysozyme nitrate crystals, α = 28.5A°, b = 32.7A°, c = 35.1A°, α = 88.2°, β = 108.9°, γ = 111.9°, belonging to the P1 space group, were determined by X-ray diffraction before and after THz measurements. The intramolecular vibrational absorbance of the triclinic crystals has a more complex polarization dependence than the higher symmetry tetragonal crystals, as expected. While the tetragonal crystals have two strong bands at 45cm−1 and 55cm−1, the triclinic crystals have a series of narrow bands between 40 and 60cm−1 and a prominent band at 30cm−1. We compare the measured spectra to normal mode ensemble averaged calculations to assign the observed resonances, and isolating which collective motions impact the catalytic site.
ISI Document Delivery No.: HO2XG Times Cited: 0 Cited Reference Count: 1 Cited References: Niessen KA, 2017, BIOPHYS J, V112, P933, DOI 10.1016/j.bpj.2016.12.049 Deng, Yanting Mckinney, Jeffrey Romo, Tod Grossfield, Alan Markelz, Andrea 63rd Annual Meeting of the Biophysical-Society Mar 02-06, 2019 Baltimore, MD Biophys Soc 8 Cell press Cambridge 1542-0086 1
Keywords: Biophysics

Increase in Dynamical Collectivity and Directionality of Orange Carotenoid Protein in the Photo-Protective State - Deng, Y. T.; Luck, C. H.; Romo, T. D.; Grossfield, A. M.; Bandara, S.; Ren, Z.; Yang, X. J.; Markelz, A. G. (Biophysical Journal, 2018)
ISI Document Delivery No.: GD5RB Times Cited: 1 Cited Reference Count: 0 Deng, Yanting Luck, Catherine H. Romo, Tod D. Grossfield, Alan M. Bandara, Sepalika Ren, Zhong Yang, Xiaojing Markelz, Andrea G. 62nd Annual Meeting of the Biophysical-Society Feb 17-21, 2018 San Francisco, CA Biophys Soc 1 7 Cell press Cambridge 1542-0086
Keywords: Biophysics

The 2017 terahertz science and technology roadmap - Dhillon, S. S.; Vitiello, M. S.; Linfield, E. H.; Davies, A. G.; Hoffmann, M. C.; Booske, J.; Paoloni, C.; Gensch, M.; Weightman, P.; Williams, G. P.; Castro-Camus, E.; Cumming, D. R. S.; et al. (Journal of Physics D-Applied Physics, 2017)
Science and technologies based on terahertz frequency electromagnetic radiation (100 GHz-30 THz) have developed rapidly over the last 30 years. For most of the 20th Century, terahertz radiation, then referred to as sub-millimeter wave or far-infrared radiation, was mainly utilized by astronomers and some spectroscopists. Following the development of laser based terahertz time-domain spectroscopy in the 1980s and 1990s the field of THz science and technology expanded rapidly, to the extent that it now touches many areas from fundamental science to 'real world' applications. For example THz radiation is being used to optimize materials for new solar cells, and may also be a key technology for the next generation of airport security scanners. While the field was emerging it was possible to keep track of all new developments, however now the field has grown so much that it is increasingly difficult to follow the diverse range of new discoveries and applications that are appearing. At this point in time, when the field of THz science and technology is moving from an emerging to a more established and interdisciplinary field, it is apt to present a roadmap to help identify the breadth and future directions of the field. The aim of this roadmap is to present a snapshot of the present state of THz science and technology in 2017, and provide an opinion on the challenges and opportunities that the future holds. To be able to achieve this aim, we have invited a group of international experts to write 18 sections that cover most of the key areas of THz science and technology. We hope that The 2017 Roadmap on THz science and technology will prove to be a useful resource by providing a wide ranging introduction to the capabilities of THz radiation for those outside or just entering the field as well as providing perspective and breadth for those who are well established. We also feel that this review should serve as a useful guide for government and funding agencies.
ISI Document Delivery No.: EI0HL Times Cited: 541 Cited Reference Count: 209 Cited References: Adam AJL, 2011, J INFRARED MILLIM TE, V32, P976, DOI 10.1007/s10762-011-9809-2 Ahmed SS, 2012, IEEE MICROW MAG, V13, P26, DOI 10.1109/MMM.2012.2205772 Alliance N., 2015, CISC VIS NETW IND GL, P1 [Anonymous], 2013, 178512012 IEEE [Anonymous], 2014, IEEE T ELECT DEVICES, V61 [Anonymous], 2012, 178522016 IEEE [Anonymous], 2015, P17852 IEEE Appleby R, 2015, P SOC PHOTO-OPT INS, V9462 Arnone DD, 1999, PROC SPIE, V3828, P209, DOI 10.1117/12.361037 Ashworth PC, 2009, OPT EXPRESS, V17, P12444, DOI 10.1364/OE.17.012444 AUSTON DH, 1988, IEEE J QUANTUM ELECT, V24, P184, DOI 10.1109/3.114 Barbieri S, 2011, NAT PHOTONICS, V5, P306, DOI [10.1038/NPHOTON.2011.49, 10.1038/nphoton.2011.49] Barker RJ., 2005, MODERN MICROWAVE MIL Basov DN, 2011, REV MOD PHYS, V83, P471, DOI 10.1103/RevModPhys.83.471 Bauwens M. F., 2014, P IEEEMTT S INT MICR, P1, DOI [10.1109/MWSYM.2014.68486 07, DOI 10.1109/MWSYM.2014.6848607] Beard MC, 2002, NANO LETT, V2, P983, DOI 10.1021/nl0256210 Beard MC, 2000, PHYS REV B, V62, P15764, DOI 10.1103/PhysRevB.62.15764 Bechtel HA, 2014, P NATL ACAD SCI USA, V111, P7191, DOI 10.1073/pnas.1400502111 Belkin MA, 2008, OPT EXPRESS, V16, P3242, DOI 10.1364/OE.16.003242 Belkin MA, 2015, PHYS SCRIPTA, V90, DOI 10.1088/0031-8949/90/11/118002 Bell R., 2012, INTRO FOURIER TRANSF Berry CW, 2013, NAT COMMUN, V4, DOI 10.1038/ncomms2638 Blanchard F, 2011, OPT EXPRESS, V19, P8277, DOI 10.1364/OE.19.008277 Blau J, 2013, P FREE EL LAS FEL 20, P486 Booske JH, 2011, IEEE T THZ SCI TECHN, V1, P54, DOI 10.1109/TTHZ.2011.2151610 Booske JH, 2008, PHYS PLASMAS, V15, DOI 10.1063/1.2838240 Boppel S, 2012, 2012 IEEE 12TH TOPICAL MEETING ON SILICON MONOLITHIC INTEGRATED CIRCUITS IN RF SYSTEMS (SIRF), P77, DOI 10.1109/SiRF.2012.6160142 Burghoff D, 2014, NAT PHOTONICS, V8, P462, DOI 10.1038/nphoton.2014.85 Busch SF, 2014, J INFRARED MILLIM TE, V35, P993, DOI 10.1007/s10762-014-0113-9 Byrne MB, 2011, APPL PHYS LETT, V98, DOI 10.1063/1.3579258 Carr GL, 2002, NATURE, V420, P153, DOI 10.1038/nature01175 Carranza IE, 2015, IEEE T THZ SCI TECHN, V5, P892, DOI 10.1109/TTHZ.2015.2463673 Castro-Camus E, 2007, OPT EXPRESS, V15, P7047, DOI 10.1364/OE.15.007047 Chan WL, 2007, REP PROG PHYS, V70, P1325, DOI 10.1088/0034-4885/70/8/R02 Chattopadhyay G, 2011, IEEE T THZ SCI TECHN, V1, P33, DOI 10.1109/TTHZ.2011.2159561 Chen HT, 2003, APPL PHYS LETT, V83, P3009, DOI 10.1063/1.1616668 Chen JN, 2012, NATURE, V487, P77, DOI 10.1038/nature11254 Cocker T L, 2016, J PHYS D, V16, P1421 Cocker TL, 2013, NAT PHOTONICS, V7, P620, DOI [10.1038/NPHOTON.2013.151, 10.1038/nphoton.2013.151] Coleman B, 2001, Issue Brief (Public Policy Inst (Am Assoc Retired Pers)), P1 Cooper KB, 2014, IEEE MICROW MAG, V15, P51, DOI 10.1109/MMM.2014.2356092 Cruz F C, 2007, C MICR OPT Cunningham J, 2010, ELECTRON LETT, V46, pS34, DOI 10.1049/el.2010.3317 Dean P, 2011, OPT LETT, V36, P2587, DOI 10.1364/OL.36.002587 Dietz RJB, 2014, OPT LETT, V39, P6482, DOI 10.1364/OL.39.006482 Dietz RJB, 2014, OPT EXPRESS, V22, P19411, DOI 10.1364/OE.22.019411 Dobrovolsky V, 2007, SEMICOND SCI TECH, V22, P103, DOI 10.1088/0268-1242/22/2/017 Ducournau G, 2014, IEEE T THZ SCI TECHN, V4, P328, DOI 10.1109/TTHZ.2014.2309006 Dunsmore J.P., 2012, HDB MICROWAVE COMPON Duvillaret L, 1999, APPL OPTICS, V38, P409, DOI 10.1364/AO.38.000409 Eisele M, 2014, NAT PHOTONICS, V8, P841, DOI [10.1038/nphoton.2014.225, 10.1038/NPHOTON.2014.225] Falconer RJ, 2012, J INFRARED MILLIM TE, V33, P973, DOI 10.1007/s10762-012-9915-9 Fathololoumi S, 2012, OPT EXPRESS, V20, P3866, DOI 10.1364/OE.20.003866 Fausti D, 2011, SCIENCE, V331, P189, DOI 10.1126/science.1197294 Federici J, 2010, J APPL PHYS, V107, DOI 10.1063/1.3386413 Fei Z, 2012, NATURE, V487, P82, DOI 10.1038/nature11253 FETTERMAN HR, 1974, APPL PHYS LETT, V24, P70, DOI 10.1063/1.1655098 Freeman JR, 2013, OPT EXPRESS, V21, P16162, DOI 10.1364/OE.21.016162 Frisk U, 2003, ASTRON ASTROPHYS, V402, pL27, DOI 10.1051/0004-6361:20030335 Garet F, 2014, APPL PHYS LETT, V105, DOI 10.1063/1.4890732 Gavrilov NG, 2007, NUCL INSTRUM METH A, V575, P54, DOI 10.1016/j.nima.2007.01.023 Gensch M., 2013, P 35 INT FREE EL LAS, P474 George DK, 2012, J OPT SOC AM B, V29, P1406, DOI 10.1364/JOSAB.29.001406 Giliberti V, 2013, APPL PHYS LETT, V103, DOI 10.1063/1.4819734 Grant J, 2013, LASER PHOTONICS REV, V7, P1043, DOI 10.1002/lpor.201300087 Green B, 2016, SCI REP-UK, V6, DOI 10.1038/srep22256 Griffith P.R., 2007, FOURIER TRANSFORM IN GRISCHKOWSKY D, 1990, J OPT SOC AM B, V7, P2006, DOI 10.1364/JOSAB.7.002006 Gruene P, 2008, SCIENCE, V321, P674, DOI 10.1126/science.1161166 Han NR, 2014, OPT LETT, V39, P3480, DOI 10.1364/OL.39.003480 Han RN, 2013, IEEE J SOLID-ST CIRC, V48, P2296, DOI 10.1109/JSSC.2013.2269856 Hanham SM, 2015, APPL PHYS LETT, V107, DOI 10.1063/1.4927242 Hassel J, 2015, PROC SPIE, V9651, DOI 10.1117/12.2197522 Hauri CP, 2011, APPL PHYS LETT, V99, DOI 10.1063/1.3655331 He W, 2015, APPL PHYS LETT, V107, DOI 10.1063/1.4932099 Hebling J, 2002, OPT EXPRESS, V10, P1161, DOI 10.1364/OE.10.001161 Heinz E, 2015, J INFRARED MILLIM TE, V36, P879, DOI 10.1007/s10762-015-0170-8 Henry SC, 2012, OPT ENG, V51, DOI 10.1117/1.OE.51.9.091603 Hesler J L, 2006, P 7 INT S SPAC TER T, P215 Hintzsche H, 2012, CRIT REV ENV SCI TEC, V42, P2408, DOI 10.1080/10643389.2011.574206 Hishida M, 2011, PHYS REV LETT, V106, DOI 10.1103/PhysRevLett.106.158102 Ho IC, 2010, OPT EXPRESS, V18, P2872, DOI 10.1364/OE.18.002872 HU BB, 1995, OPT LETT, V20, P1716, DOI 10.1364/OL.20.001716 Huang C, 2012, PHYS REV B, V85 Huber R, 2001, NATURE, V414, P286, DOI 10.1038/35104522 Jankowiak A., 2013, Synchrotron Radiation News, V26, P22, DOI 10.1080/08940886.2013.791212 Jepsen PU, 2007, CHEM PHYS LETT, V442, P275, DOI 10.1016/j.cplett.2007.05.112 Jepsen PU, 2011, LASER PHOTONICS REV, V5, P124, DOI 10.1002/lpor.201000011 Jepsen PU, 2005, OPT LETT, V30, P29, DOI 10.1364/OL.30.000029 JUICE-Jupiter Icy Moons Explorer, 2014, SRE20141 JUICE EUR S, P1 Kallfass I, 2011, IEEE T THZ SCI TECHN, V1, P477, DOI 10.1109/TTHZ.2011.2160021 Kampfrath T, 2013, NAT PHOTONICS, V7, P680, DOI [10.1038/nphoton.2013.184, 10.1038/NPHOTON.2013.184] Kan T, 2015, NAT COMMUN, V6, DOI 10.1038/ncomms9422 Karpowicz N, 2008, APPL PHYS LETT, V92, DOI 10.1063/1.2828709 Kehr SC, 2008, PHYS REV LETT, V100, DOI 10.1103/PhysRevLett.100.256403 Kemp MC, 2011, IEEE T THZ SCI TECHN, V1, P282, DOI 10.1109/TTHZ.2011.2159647 Khalid A, 2014, J APPL PHYS, V115, DOI 10.1063/1.4868705 Kirley MP, 2015, IEEE T THZ SCI TECHN, V5, P1012, DOI 10.1109/TTHZ.2015.2468074 Kiwa T, 2003, OPT LETT, V28, P2058, DOI 10.1364/OL.28.002058 Koch M, 2001, NATO SCI SER II MATH, V27, P241 Koenig S, 2013, NAT PHOTONICS, V7, P977, DOI [10.1038/nphoton.2013.275, 10.1038/NPHOTON.2013.275] Kohler R, 2002, NATURE, V417, P156, DOI 10.1038/417156a Koppens FHL, 2014, NAT NANOTECHNOL, V9, P780, DOI [10.1038/nnano.2014.215, 10.1038/NNANO.2014.215] Kosarev A, 2010, SOLID STATE ELECTRON, V54, P417, DOI 10.1016/j.sse.2009.12.032 Kundu I, 2014, OPT EXPRESS, V22, P16595, DOI 10.1364/OE.22.016595 Kuznetsov SA, 2010, KEY ENG MATER, V437, P276, DOI 10.4028/www.scientific.net/KEM.437.276 Langevin Y, 2005, PAYLOAD MISSION DEFI LaRue JL, 2015, PHYS REV LETT, V115, DOI 10.1103/PhysRevLett.115.036103 Leitenstorfer A, 2014, NEW J PHYS, V16, DOI 10.1088/1367-2630/16/4/045016 Leitner DM, 2006, INT REV PHYS CHEM, V25, P553, DOI 10.1080/01442350600862117 Li LH, 2014, ELECTRON LETT, V50, P309, DOI 10.1049/el.2013.4035 Liu L, 2010, IEEE MICROW WIREL CO, V20, P504, DOI 10.1109/LMWC.2010.2055553 Liu SC, 2016, OPT EXPRESS, V24, P2728, DOI 10.1364/OE.24.002728 Lu X H, 2008, P SOC PHOTO-OPT INS, V7277 Luukanen A, 2003, APPL PHYS LETT, V82, P3970, DOI 10.1063/1.1579562 Mann C, 2009, P SOC PHOTO-OPT INS, V7311, P3970 Mickan S, 2004, PROC SPIE, V5277, P54, DOI 10.1117/12.530386 Mineo M, 2010, IEEE T ELECTRON DEV, V57, P3169, DOI 10.1109/TED.2010.2071876 Mittleman DM, 1996, IEEE J SEL TOP QUANT, V2, P679, DOI 10.1109/2944.571768 Mittleman DM, 1999, APPL PHYS B-LASERS O, V68, P1085, DOI 10.1007/s003400050750 Moon K, 2012, APPL PHYS LETT, V101, DOI 10.1063/1.4733475 Muller AS, 2010, REV ACCEL SCI TECH, V3, P165, DOI 10.1142/S1793626810000427 Muller R, 2015, J INFRARED MILLIM TE, V36, P654, DOI 10.1007/s10762-015-0163-7 Naftaly M, 2015, TERAHERTZ METROLOGY, P1 Nagai M, 2015, OPT EXPRESS, V23, P4641, DOI 10.1364/OE.23.004641 Nagatsuma T, 2012, OPT EXPRESS, V21, P477 Nagel M, 2002, APPL PHYS LETT, V80, P154, DOI 10.1063/1.1428619 Navarro-Cia M, 2015, J INFRARED MILLIM TE, V36, P542, DOI 10.1007/s10762-015-0157-5 Nielsen K, 2009, OPT EXPRESS, V17, P8592, DOI 10.1364/OE.17.008592 Niessen Katherine A, 2015, Biophys Rev, V7, P201, DOI 10.1007/s12551-015-0168-4 Nordquist CD, 2011, IEEE J SEL TOP QUANT, V17, P130, DOI 10.1109/JSTQE.2010.2049095 Oh SJ, 2012, J INFRARED MILLIM TE, V33, P74, DOI 10.1007/s10762-011-9847-9 Ojefors E, 2009, IEEE J SOLID-ST CIRC, V44, P1968, DOI 10.1109/JSSC.2009.2021911 Ortolani M, 2008, PHYS REV LETT, V97 Ozerov M, 2014, PHYS REV LETT, V113, DOI 10.1103/PhysRevLett.113.157205 Paoloni C, 2013, IEEE T ELECTRON DEV, V60, P1236, DOI 10.1109/TED.2013.2240686 Parrott EPJ, 2015, APPL SPECTROSC, V69, P1, DOI 10.1366/14-07707 Patrashin M, 2015, IEEE T ELECTRON DEV, V62, P1068, DOI 10.1109/TED.2015.2393358 Peiponen K. E., 2013, TERAHERTZ SPECTROSCO, V171 Peng K, 2015, NANO LETT, V15, P206, DOI 10.1021/nl5033843 Pickwell E, 2004, APPL PHYS LETT, V84, P2190, DOI 10.1063/1.1688448 Ponnampalam L, 2011, J LIGHTWAVE TECHNOL, V29, P2229, DOI 10.1109/JLT.2011.2158186 Pupeza I, 2007, OPT EXPRESS, V15, P4335, DOI 10.1364/OE.15.004335 Rauter P, 2015, LASER PHOTONICS REV, V9, P452, DOI 10.1002/lpor.201500095 Reid CB, 2011, PHYS MED BIOL, V56, P4333, DOI 10.1088/0031-9155/56/14/008 Reid J R, 2012, IEEE 12 TOP M SIL MO, P17 Rosch M, 2015, NAT PHOTONICS, V9, P42, DOI [10.1038/nphoton.2014.279, 10.1038/NPHOTON.2014.279] Rudd JV, 2000, PROC SPIE, V3934, P27, DOI 10.1117/12.386344 Rymanov V, 2015, PHOTONICS, V2, DOI 10.3390/photonics2041152 SANTOS Daisy Conceicao, 2014, THESIS Scherger B, 2011, APPL OPTICS, V50, P2256, DOI 10.1364/AO.50.002256 Schleicher JM, 2009, J APPL PHYS, V105, DOI 10.1063/1.3133093 Schumann S, 2012, OPT EXPRESS, V20, P19200, DOI 10.1364/OE.20.019200 Seeds AJ, 2015, J LIGHTWAVE TECHNOL, V33, P579, DOI 10.1109/JLT.2014.2355137 Sell A, 2008, OPT LETT, V33, P2767, DOI 10.1364/OL.33.002767 Shams H, 2015, IEEE PHOTONICS J, V7, DOI 10.1109/JPHOT.2015.2438437 Shams H, 2014, OPT EXPRESS, V22, P23465, DOI 10.1364/OE.22.023465 Shen YC, 2004, APPL PHYS LETT, V85, P164, DOI 10.1063/1.1768313 Simoens F., 2014, PHILOS T A, V372, P1 Simoens F, 2011, 36 INT C INFR MILL T, P1 Singh A, 2015, OPT EXPRESS, V23, P6656, DOI 10.1364/OE.23.006656 Sirtori C, 2013, NAT PHOTONICS, V7, P691, DOI [10.1038/NPHOTON.2013.208, 10.1038/nphoton.2013.208] SMITH PR, 1988, IEEE J QUANTUM ELECT, V24, P255, DOI 10.1109/3.121 Son JH, 2013, NANOTECHNOLOGY, V24, DOI 10.1088/0957-4484/24/21/214001 Swinyard B, 2013, SPIE SENSORS SYSTEMS Sy S, 2010, PHYS MED BIOL, V55, P7587, DOI 10.1088/0031-9155/55/24/013 Taylor ZD, 2015, IEEE T THZ SCI TECHN, V5, P184, DOI 10.1109/TTHZ.2015.2392628 Teppati V, 2013, CAMB RF MICROW ENG, P1, DOI 10.1017/CBO9781139567626 Tewari P, 2012, P SPIE, V8261 Thomas B., 2014, P 39 INT C INFR MILL, P1 Thumm M, 2014, KIT SCI REPORTS, V7693 Tonouchi M, 2007, NAT PHOTONICS, V1, P97, DOI 10.1038/nphoton.2007.3 Truong BCQ, 2015, IEEE T BIO-MED ENG, V62, P699, DOI 10.1109/TBME.2014.2364025 Turcinkova D, 2015, APPL PHYS LETT, V106, DOI 10.1063/1.4916653 Turner GM, 2002, J PHYS CHEM B, V106, P11716, DOI 10.1021/jp025844e van der Valk NCJ, 2002, APPL PHYS LETT, V81, P1558, DOI 10.1063/1.1503404 van Dijk F, 2014, IEEE PHOTONIC TECH L, V26, P965, DOI 10.1109/LPT.2014.2309353 Vicario C, 2014, PHYS REV LETT, V112, DOI 10.1103/PhysRevLett.112.213901 Vinh NQ, 2015, J CHEM PHYS, V142, DOI 10.1063/1.4918708 Vitiello MS, 2012, NAT PHOTONICS, V6, P525, DOI 10.1038/nphoton.2012.145 Vitiello MS, 2015, OPT EXPRESS, V23, P5167, DOI 10.1364/OE.23.005167 Vitiello MS, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms6884 Wade A, 2009, NAT PHOTONICS, V3, P41, DOI 10.1038/NPHOTON.2008.251 Wallace B., 2015, SPIE NEWSROOM, DOI [10.1117/2.1201503.005871, DOI 10.1117/2.1201503.005871] Wallace VP, 2004, BRIT J DERMATOL, V151, P424, DOI 10.1111/j.1365-2133.2004.06129.x Wang FH, 2015, OPTICA, V2, P944, DOI 10.1364/OPTICA.2.000944 Weightman P, 2012, PHYS BIOL, V9, DOI 10.1088/1478-3975/9/5/053001 Wienold M, 2014, OPT EXPRESS, V22, P3334, DOI 10.1364/OE.22.003334 Wilk R, 2007, C LAS EL BALT MD Williams BS, 2006, ELECTRON LETT, V42, P89, DOI 10.1049/el:20063921 Williams GP, 2006, REP PROG PHYS, V69, P301, DOI 10.1088/0034-4885/69/2/R01 Williams GP, 2008, NAT PHYS, V4, P356, DOI 10.1038/nphys958 Williams MRC, 2013, J PHYS CHEM B, V117, P10444, DOI 10.1021/jp406730a Williams R, 2013, PHYS MED BIOL, V58, P373, DOI 10.1088/0031-9155/58/2/373 Withayachumnankul W, 2008, J OPT SOC AM B, V25, P1059, DOI 10.1364/JOSAB.25.001059 Woerner M, 2013, NEW J PHYS, V15, DOI 10.1088/1367-2630/15/2/025039 Woodward RM, 2003, J INVEST DERMATOL, V120, P72, DOI 10.1046/j.1523-1747.2003.12013.x Wu X, OPT LETT, V39, P5403 Wu ZR, 2013, REV SCI INSTRUM, V84, DOI 10.1063/1.4790427 Xu J, 2003, PROC SPIE, V5268, P19, DOI 10.1117/12.518533 Yamashita M, 2011, OPT EXPRESS, V19, P10864, DOI 10.1364/OE.19.010864 Yan F, 2013, J INFRARED MILLIM TE, V34, P489, DOI 10.1007/s10762-013-0005-4 Yang SH, 2014, IEEE T THZ SCI TECHN, V4, P575, DOI 10.1109/TTHZ.2014.2342505 Yeh KL, 2007, APPL PHYS LETT, V90, DOI 10.1063/1.2734374 Zamora A, 2015, IEEE MTT S INT MICR Zhao JF, 2011, IEEE T ELECTRON DEV, V58, P1221, DOI 10.1109/TED.2011.2109723 Zheludev NI, 2012, NAT MATER, V11, P917, DOI [10.1038/NMAT3431, 10.1038/nmat3431] Zhou Y, 2010, PROG ELECTROMAGN RES, V105, P71, DOI 10.2528/PIER10041806 Zibik EA, 2009, NAT MATER, V8, P803, DOI [10.1038/nmat2511, 10.1038/NMAT2511] Dhillon, S. S. Vitiello, M. S. Linfield, E. H. Davies, A. G. Hoffmann, Matthias C. Booske, John Paoloni, Claudio Gensch, M. Weightman, P. Williams, G. P. Castro-Camus, E. Cumming, D. R. S. Simoens, F. Escorcia-Carranza, I. Grant, J. Lucyszyn, Stepan Kuwata-Gonokami, Makoto Konishi, Kuniaki Koch, Martin Schmuttenmaer, Charles A. Cocker, Tyler L. Huber, Rupert Markelz, A. G. Taylor, Z. D. Wallace, Vincent P. Zeitler, J. Axel Sibik, Juraj Korter, Timothy M. Ellison, B. Rea, S. Goldsmith, P. Cooper, Ken B. Appleby, Roger Pardo, D. Huggard, P. G. Krozer, V. Shams, Haymen Fice, Martyn Renaud, Cyril Seeds, Alwyn Stoehr, Andreas Naftaly, Mira Ridler, Nick Clarke, Roland Cunningham, John E. Johnston, Michael B. Huggard, Peter/U-2150-2019; Konishi, Kuniaki/AAN-3624-2020; Zeitler, J. Axel/B-4885-2008; Paoloni, Claudio/AAH-9824-2019; Hoffmann, Matthias C./N-1082-2019; Wallace, Vincent P/A-9320-2012; Johnston, Michael/B-9813-2008; Castro-Camus, Enrique/V-6861-2019; Krozer, Viktor/P-5623-2014; Hoffmann, Matthias C/B-3893-2009; PAOLONI, CLAUDIO/AAA-3211-2020; Gonokami, Makoto/F-3641-2012; Shams, Haymen/H-3754-2012; Ridler, Nick/AAN-9637-2020; Huber, Rupert/N-4126-2018 Konishi, Kuniaki/0000-0003-2389-9787; Zeitler, J. Axel/0000-0002-4958-0582; Hoffmann, Matthias C./0000-0002-3596-9853; Wallace, Vincent P/0000-0003-3814-5400; Johnston, Michael/0000-0002-0301-8033; Krozer, Viktor/0000-0002-2387-1947; Hoffmann, Matthias C/0000-0002-3596-9853; PAOLONI, CLAUDIO/0000-0002-0265-0862; Shams, Haymen/0000-0002-5333-6478; Huber, Rupert/0000-0001-6617-9283; Davies, Alexander/0000-0002-1987-4846; Seeds, Alwyn/0000-0002-5228-627X; Castro-Camus, Enrique/0000-0002-8218-9155; Cunningham, John/0000-0002-1805-9743; Naftaly, Mira/0000-0002-0671-822X; Cumming, David/0000-0002-7838-8362 Engineering and Physical Sciences Research CouncilUK Research & Innovation (UKRI)Engineering & Physical Sciences Research Council (EPSRC) [EP/P015883/1, EP/M00306X/1, EP/K023349/1, EP/M017095/1, EP/L026597/1, EP/J017671/1] Funding Source: researchfish; Natural Environment Research CouncilUK Research & Innovation (UKRI)NERC Natural Environment Research Council [NER/Z/S/2003/00642, NE/L012375/1, NER/Z/S/2000/01292] Funding Source: researchfish; Science and Technology Facilities CouncilUK Research & Innovation (UKRI)Science & Technology Facilities Council (STFC) [ST/P002056/1] Funding Source: researchfish; Direct For Biological SciencesNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1556359] Funding Source: National Science Foundation; Div Of Biological InfrastructureNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1556359] Funding Source: National Science Foundation; Div Of Molecular and Cellular BioscienceNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1616529] Funding Source: National Science Foundation 566 30 462 Iop publishing ltd Bristol 1361-6463
Keywords: ex-vivo; generation; metal wave-guides; near-field; performance; photoconductive emitters; Physics; quantum-cascade lasers; radiation; semiconductors; Terahertz; thz; time-domain spectroscopy

The role of the protein surface on the local biological water dynamics - Liang, W.; He, Y. F.; George, D.; Markelz, A. G. (Biosensing Ii, 2009)
Protein function is reliant on structural flexibility and this flexibility is slaved to the surrounding solvent. Here we discuss how the exposed surface of the protein influences the solvent dynamics and thereby influences the protein's own structural dynamics. We discuss measurements of the THz absorption of water in the presence of hydrophilic and hydrophobic surfaces.
ISI Document Delivery No.: BVQ85 Times Cited: 0 Cited Reference Count: 12 Cited References: Balu R, 2008, BIOPHYS J, V94, P3217, DOI 10.1529/biophysj.107.105163 Bergner A, 2005, REV SCI INSTRUM, V76, DOI 10.1063/1.1928427 Born B, 2009, J AM CHEM SOC, V131, P3752, DOI 10.1021/ja808997y Chen JY, 2007, APPL PHYS LETT, V90, DOI 10.1063/1.2748852 He YF, 2008, PHYS REV LETT, V101, DOI 10.1103/PhysRevLett.101.178103 Heugen U, 2006, P NATL ACAD SCI USA, V103, P12301, DOI 10.1073/pnas.0604897103 Jepsen PU, 2007, OPT EXPRESS, V15, P14717, DOI 10.1364/OE.15.014717 Kindt JT, 1996, J PHYS CHEM-US, V100, P10373, DOI 10.1021/jp960141g Knab J, 2006, BIOPHYS J, V90, P2576, DOI 10.1529/biophysj.105.069088 THRANE L, 1995, CHEM PHYS LETT, V240, P330, DOI 10.1016/0009-2614(95)00543-D Xu J, 2006, J CHEM PHYS, V124, DOI 10.1063/1.2151267 Yada H, 2008, CHEM PHYS LETT, V464, P166, DOI 10.1016/j.cplett.2008.09.015 Liang, Wei He, Yunfen George, Deepu Markelz, A. G. Proceedings Paper Conference on Biosensing II Aug 04-06, 2009 San Diego, CA Spie George, Deepu/J-9882-2014 George, Deepu/0000-0003-0021-0705; Markelz, Andrea/0000-0003-0443-4319 1000 20th st, po box 10, bellingham, wa 98227-0010 usa 0277-786x 73970t
Keywords: alanine; dynamics; hydration; lysine; lysozyme; proteins; relaxation; spectroscopy; Terahertz; thz

Terahertz response of quantum point contacts - Song, J. W.; Kabir, N. A.; Kawano, Y.; Ishibashi, K.; Aizin, G. R.; Mourokh, L.; Reno, J. L.; Markelz, A. G.; Bird, J. P. (Applied Physics LettersApplied Physics LettersApplied Physics Letters, 2008)
We measure a clear terahertz response in the low-temperature conductance of a quantum point contact at 1.4 and 2.5 THz. We show that this photoresponse does not arise from a heating effect, but that it is instead excellently described by a classical model of terahertz-induced gate-voltage rectification. This effect is distinct from the rectification mechanisms that have been studied previously, being determined by the phase-dependent interference of the source drain and gate voltage modulations induced by the terahertz field. (C) 2008 American Institute of Physics.
ISI Document Delivery No.: 310KL Times Cited: 25 Cited Reference Count: 21 Cited References: Aizin GR, 2007, APPL PHYS LETT, V91, DOI 10.1063/1.2800369 ARNONE DD, 1995, APPL PHYS LETT, V66, P3149, DOI 10.1063/1.113705 FENG SC, 1993, PHYS REV B, V48, P5354, DOI 10.1103/PhysRevB.48.5354 Hashiba H, 2004, APPL PHYS LETT, V85, P6036, DOI 10.1063/1.1834716 HU Q, 1993, APPL PHYS LETT, V62, P837, DOI 10.1063/1.108567 Hu Q, 1996, SEMICOND SCI TECH, V11, P1888, DOI 10.1088/0268-1242/11/12/021 JANSSEN TJBM, 1994, J PHYS-CONDENS MAT, V6, pL163, DOI 10.1088/0953-8984/6/13/002 Kabir NA, 2006, APPL PHYS LETT, V89, DOI 10.1063/1.2357605 KARADI C, 1994, J OPT SOC AM B, V11, P2566, DOI 10.1364/JOSAB.11.002566 Knap W, 2002, APPL PHYS LETT, V81, P4637, DOI 10.1063/1.1525851 Knap W, 2002, APPL PHYS LETT, V80, P3433, DOI 10.1063/1.1473685 Lee M, 2005, APPL PHYS LETT, V86, DOI 10.1063/1.1851606 MITTLEMAN D, 2002, SPRINGER SERIES OPTI Peralta XG, 2002, APPL PHYS LETT, V81, P1627, DOI 10.1063/1.1497433 Ryzhii V, 2006, JPN J APPL PHYS 2, V45, pL1118, DOI 10.1143/JJAP.45.L1118 Shaner EA, 2007, APPL PHYS LETT, V90, DOI 10.1063/1.2735943 Shaner EA, 2005, APPL PHYS LETT, V87, DOI 10.1063/1.2128057 Teppe F, 2005, APPL PHYS LETT, V87, DOI 10.1063/1.2005394 VANHOUTEN H, 1992, SEMICONDUCT SEMIMET, P9 WYSS RA, 1993, APPL PHYS LETT, V63, P1522, DOI 10.1063/1.110736 WYSS RA, 1995, APPL PHYS LETT, V66, P1144, DOI 10.1063/1.113840 Song, J. W. Kabir, N. A. Kawano, Y. Ishibashi, K. Aizin, G. R. Mourokh, L. Reno, J. L. Markelz, A. G. Bird, J. P. Ishibashi, Koji/G-7065-2012; Bird, Jonathan P/G-4068-2010 Ishibashi, Koji/0000-0001-8131-9969; Bird, Jonathan P/0000-0002-6966-9007; Markelz, Andrea/0000-0003-0443-4319 27 6 Amer inst physics Melville 1077-3118
Keywords: detector; devices; field-effect transistors; Physics; plasma-waves; radiation; resonant detection; subterahertz; transport

Terahertz transmission characteristics of high-mobility GaAs and InAs two-dimensional-electron-gas systems - Kabir, N. A.; Yoon, Y.; Knab, J. R.; Chen, J. Y.; Markelz, A. G.; Reno, J. L.; Sadofyev, Y.; Johnson, S.; Zhang, Y. H.; Bird, J. P. (Applied Physics Letters, 2006)
Frequency-dependent complex conductivity of high-mobility GaAs and InAs two-dimensional-electron-gas (2DEG) systems is studied by terahertz time domain spectroscopy. Determining the momentum relaxation time from a Drude model, the authors find a lower value than that from dc measurements, particularly at high frequencies/low temperatures. These deviations are consistent with the ratio tau(t)/tau(q,) where tau(q) is the full scattering time. This suggests that small-angle scattering leads to weaker heating of 2DEGs at low temperatures than expected from dc mobilit9y. (c) 2006 American Institute of Physics.
ISI Document Delivery No.: 089JE Times Cited: 18 Cited Reference Count: 16 Cited References: ANDO T, 1982, REV MOD PHYS, V54, P437, DOI 10.1103/RevModPhys.54.437 ANDO T, 1989, HIGH MAGNETIC FIELDS, V2, P164 Ashcroft NW, 1976, SOLID STATE PHYS, P1 Beard MC, 2000, PHYS REV B, V62, P15764, DOI 10.1103/PhysRevB.62.15764 Cerne J, 2000, PHYS REV B, V61, P8133, DOI 10.1103/PhysRevB.61.8133 COLERIDGE PT, 1991, PHYS REV B, V44, P3793, DOI 10.1103/PhysRevB.44.3793 Dorozhkin PS, 2005, APPL PHYS LETT, V87, DOI 10.1063/1.2035883 Knap W, 2002, APPL PHYS LETT, V81, P4637, DOI 10.1063/1.1525851 Knap W, 2002, APPL PHYS LETT, V80, P3433, DOI 10.1063/1.1473685 Kukushkin IV, 2005, APPL PHYS LETT, V86, DOI 10.1063/1.1856143 MADELUNG O, 1996, SEMICONDUCTORS BASIC, P109 MCKNIGHT SW, 1987, INFRARED PHYS, V27, P327, DOI 10.1016/0020-0891(87)90074-1 Peralta XG, 2002, APPL PHYS LETT, V81, P1627, DOI 10.1063/1.1497433 Sadofyev YG, 2002, APPL PHYS LETT, V81, P1833, DOI 10.1063/1.1504882 Shaner EA, 2005, APPL PHYS LETT, V87, DOI 10.1063/1.2128057 ZAWADZKI W, 1974, ADV PHYS, V23, P435, DOI 10.1080/00018737400101371 Kabir, N. A. Yoon, Y. Knab, J. R. Chen, J. -Y. Markelz, A. G. Reno, J. L. Sadofyev, Y. Johnson, S. Zhang, Y. -H. Bird, J. P. Bird, Jonathan P/G-4068-2010 Bird, Jonathan P/0000-0002-6966-9007; Markelz, Andrea/0000-0003-0443-4319 18 15 Amer inst physics Melville
Keywords: field-effect transistors; photoconductivity; Physics; plasma-waves; radiation; resonant detection; subterahertz

Direct measurements of optical phonons in SrTiO3 nanosystems - Wolpert, D; Korolev, K; Sachs, S; Knab, J; Cox, W; Cerne, J; Markelz, A.G; Zhao, T; Ramesh, R; Moeckly, B.H (Physica E: Low-dimensional Systems and Nanostructures, 2003)
We use terahertz time domain spectroscopy to examine finite size effects on the optical phonon modes in SrTiO3 thin films. In temperature-dependent measurements we find a near absence of mode softening in the TO1 phonon frequency. Furthermore we see an increase in the soft mode frequency with reduced thickness. Both of these results correlate well with the reduced dielectric response observed for nanoscale ferroelectric systems.
Keywords: Ferroelectrics; Finite size; Mode softening; phonons; Strontium titanate; Terahertz

Finite size effects in ferroelectric nanosystems: Absence of mode softening - D. Wolpert; W. Cox; J. Cerne; A. Markelz; T. Zhao; R. Ramesh (2003 Nanotechnology Conference and Trade Show - Nanotech, 2003)
We present measurements of the mode softening behavior for PbZr 0.5Ti0.5O3 (PZT(50)) thin films using terahertz time domain spectroscopy (TTDS). The films were grown using pulsed laser deposition (PLD) techniques on silicon substrates to study how reduced size affects the mode softening behavior. At room temperature two modes are observed at 1.1 THz (37 cm-1) and at 2.3 THz (77 cm-1). As the temperature is increased toward Tc we do not see strong mode softening, but rather a spectral weight transfer from the high frequency mode to the low frequency mode. This absence of mode softening is more dramatic than that reported by other investigators[1]. We will discuss the possible sources for this discrepancy. These results suggest a change in lattice dynamics for nanoscale ferroelectric films that may be highly dependent on the sample preparation technique.
cited By 0
Keywords: Ferroelectric materials; Fourier Transform Infrared Spectroscopy; Frequency ranges; Lead compounds; Mode softening; nanostructured materials; Natural frequencies; Optical modes; Permittivity; phase transitions; phonons; Routers; Thermal effects

Pulsed terahertz spectroscopy of DNA, bovine serum albumin and collagen between 0.1 and 2.0 THz - Markelz, A. G.; Roitberg, A.; Heilweil, E. J. (Chemical Physics Letters, 2000)
We report the first use of pulsed terahertz spectroscopy to examine low-frequency collective vibrational modes of biomolecules. Broadband absorption increasing with frequency was observed for lyophilized powder samples of calf thymus DNA, bovine serum albumin and collagen in the 0.06-2.00 THz (2-67 cm(-1)) frequency range, suggesting that a large number of the low-frequency collective modes for these systems are IR active. Transmission measurements at room temperature showed increasing FIR absorption with hydration and denaturing. (C) 2000 published by Elsevier Science B.V. All rights reserved.
ISI Document Delivery No.: 299RG Times Cited: 561 Cited Reference Count: 24 Cited References: Cai Y, 1998, APPL PHYS LETT, V73, P444, DOI 10.1063/1.121894 CARTER DC, 1994, ADV PROTEIN CHEM, V45, P153 Chen EF, 1998, BIOCHEMISTRY-US, V37, P5589, DOI 10.1021/bi972369f CHEVILLE RA, 1995, OPT LETT, V20, P1646, DOI 10.1364/OL.20.001646 FENG Y, 1991, PHYS REV A, V43, P1049, DOI 10.1103/PhysRevA.43.1049 Fraser R.D.B., 1973, CONFORMATION FIBROUS Frushour B., 1975, ADV INFRARED RAMAN S, V1 GENZEL L, 1984, SPECTROSCOPY BIOL MO, P609 GRIEBENOW K, 1995, P NATL ACAD SCI USA, V92, P10969, DOI 10.1073/pnas.92.24.10969 HAYWARD S, 1995, ANNU REV PHYS CHEM, V46, P223, DOI 10.1146/annurev.pc.46.100195.001255 KATZENELLENBOGE.N, 1992, ULTRA WIDEBAND SHORT Kindt JT, 1996, J PHYS CHEM-US, V100, P10373, DOI 10.1021/jp960141g LINDSAY SM, 1988, BIOPOLYMERS, V27, P1015, DOI 10.1002/bip.360270610 Lisy V, 1997, J BIOMOL STRUCT DYN, V14, P517, DOI 10.1080/07391102.1997.10508150 Markelz AG, 1998, APPL PHYS LETT, V72, P2229, DOI 10.1063/1.121329 Nossal R. J., 1991, MOL CELL BIOPHYSICS POWELL JW, 1987, PHYS REV A, V35, P3929, DOI 10.1103/PhysRevA.35.3929 POWELL JW, 1991, J MOL STRUCT, V247, P119 ROITBERG A, 1995, SCIENCE, V268, P1319, DOI 10.1126/science.7539156 WEIDLICH T, 1990, BIOPOLYMERS, V30, P477, DOI 10.1002/bip.360300324 WEIDLICH T, 1990, J BIOMOL STRUCT DYN, V8, P139, DOI 10.1080/07391102.1990.10507795 WITTLIN A, 1986, PHYS REV A, V34, P493, DOI 10.1103/PhysRevA.34.493 YOUNG L, 1990, PHYS REV A, V41, P7020, DOI 10.1103/PhysRevA.41.7020 ZHUANG W, 1990, PHYS REV A, V41, P7033, DOI 10.1103/PhysRevA.41.7033 Markelz, AG Roitberg, A Heilweil, EJ Roitberg, Adrian/A-2378-2009 Markelz, Andrea/0000-0003-0443-4319 598 7 235 Elsevier science bv Amsterdam
Keywords: b-dna; Chemistry; films; modes; Physics; proteins

Terahertz grid frequency doublers - Chiao, Jung-Chih; Markelz, Andrea; Li, Yongjun; Hacker, Jonathan; Crowe, Thomas; Allen, James; Rutledge, David (Proc. Sixth Intl. Symp. Space Terahertz Tech, 1995)

PROBING TERAHERTZ DYNAMICS IN SEMICONDUCTOR NANOSTRUCTURES WITH UCSB FREE-ELECTRON LASERS - Allen, S. J.; Craig, K.; Felix, C. L.; Guimaraes, P.; Heyman, J. N.; Kaminski, J. P.; Keay, B. J.; Markelz, A. G.; Ramian, G.; Scott, J. S.; Sherwin, M. S.; Campman, K. L.; et al. (Journal of Luminescence, 1994)
The UCSB free-electron lasers provide kilowatts of continuously tunable radiation from 120 GHz to 4.8 THz. They have the most impact on terahertz science and technology that require a tunable, high power source to explore non-linear dynamics or that sacrifice incident power to recover the linear response of systems with very small cross-section. We describe three experiments that demonstrate the utility of these lasers in experiments on the terahertz dynamics of semiconductor nanostructures: (i) terahertz dynamics of resonant tunneling diodes, (ii) saturation spectroscopy of quantum wells and (iii) photon-assisted tunneling in superlattices.
Sherwin, Mark S/Q-4762-2017; Guimaraes, Paulo Sergio Soares/B-6918-2012 Sherwin, Mark S/0000-0002-3869-1893; Guimaraes, Paulo Sergio Soares/0000-0002-0113-2641; Markelz, Andrea/0000-0003-0443-4319 1993 International Conference on Luminescence (ICL 93) Aug 09-13, 1993 Univ connecticut, storrs, ct Univ connecticut; opt soc amer; amer phys soc; ieee, laser & electro opt soc; int union pure & appl phys; int sci fdn; univ connecticut res fdn 3